1991
DOI: 10.1136/hrt.66.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Still's murmurs: a controlled Doppler echocardiographic study.

Abstract: Objective-The origin of innocent systolic murmurs is uncertain. This study was designed to evaluate the relative contribution in the same subjects of the main factors implicated in the genesis of vibratory innocent systolic murmursthat is, the presence of left ventricular bands and increased left ventricular flow indices-and to examine evidence for turbulence in relation to these findings.Patients-40 children with innocent systolic murmurs and 40 paired controls without murmurs were matched for age and body su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
12
2
Order By: Relevance
“…LVFTs have been associated with clinical,11,13,24,27-32 electrocardiographic11,14,20,22,30,33-37 and echocardiographic29,38,39 abnormalities. Therefore, we examined the association of LVFTs with all-cause mortality on follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LVFTs have been associated with clinical,11,13,24,27-32 electrocardiographic11,14,20,22,30,33-37 and echocardiographic29,38,39 abnormalities. Therefore, we examined the association of LVFTs with all-cause mortality on follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…These include an increased prevalence of precordial murmurs,11,13,24,27-32 repolarization abnormalities on the resting electrocardiogram,33,34 pre-excitation,30 ventricular arrhythmias,11,14,20,22,35-37 mitral regurgitation,38 and a dilated left ventricle 29,39. Most of these clinical associations have been described, however, only in small clinical case series.…”
Section: Introductionmentioning
confidence: 99%
“…As in this study, the most widely accepted association is with innocent murmur in children. [16][17][18] This murmur has been related to increased velocity in the aorta 28 ; in our study, the presence of FT was not a confounding factor but rather indicated that this velocity is slower. In fact, the movement produced by blood outflow may produce vibratory movement in the FT that causes the murmur and reduces blood flow at the aortic velocity.…”
Section: Discussionmentioning
confidence: 62%
“…The percentage of FT visualization in humans has been rising with technical improvements: the earliest studies report rates of 0.5% whereas current investigations have achieved up to 78%. [7][8][9][10][11][12][15][16][17] False tendon has been related to clinical signs, such as innocent murmur, [16][17][18] conduction and heart rate abnormalities, 19,20 cavitary thrombi, 21 and even infections, 22 although there is no consensus on the implication of FT in human physiology or disease. Its morphogenesis and embryonic origin are not well known, and prenatal imaging has been rare, with only a few reports of the condition observed during the fetal period.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies the murmur seemed to be related to higher peak velocities in the ascending and descending aorta caused in turn by a narrower aortic diameter (Schwartz et al 1986;Sholler, CeIemajer & Wright 1987). Or the murmur may be related to higher aortic flow volume and velocity but not caused by a smaller aortic size (Gardiner & Joffe 1991). It may be that turbulence in the aortic root is responsible or that in hearts with some structural abnormality, vibration of intracardiac structures causes the murmur (Stein & Sabbah 1977;Stein et al 1982;Sheikh et al 1984;Pennestri et al 1989).…”
Section: Incidence and Causes Of Innocent Murmurs In Childrenmentioning
confidence: 99%